Answer:
Option A. √(x + 1)
Step-by-step explanation:
Data obtained from the question include:
f(x) = √(x² – 1)
g(x) = √(x – 1)
(f/g) (x) =..?
(x² – 1) => difference of two square
(x² – 1) => (x – 1)(x + 1)
f(x) = √(x² – 1)
f(x) = √(x – 1)(x + 1)
(f/g) (x) = f(x) /g(x)
f(x) = √(x – 1)(x + 1)
g(x) = √(x – 1)
(f/g) (x) = √(x – 1)(x + 1) / √(x – 1)
(f/g) (x) = √[(x – 1)(x + 1) / (x – 1)]
(f/g) (x) = √(x + 1)
Answer:
The answer is 4
Step-by-step explanation:
g(x)=3x-2
g(2)=3*2-2=6-2=4
Answer:
when rounding anything that is or is greater than 5 you round up 1.
4,->7<-08.06
so rounding up 1, 4 would turn into 5.
The answer = 6.3 × 10-2
(scientific notation)
= 6.3e-2
(scientific e notation)
= 63 × 10-3
(engineering notation)
(thousandth; prefix milli- (m))
= 0.063
<span>(real number)</span>